Multiphase flow dynamics of pyroclastic density currents during the May 18, 1980 lateral blast of Mount St. Helens - Voight, Barry. (2013)
The dynamics of the May 18, 1980 lateral blast at Mount St. Helens, Washington (USA), were studied by means of a three-dimensional multiphase flow model. Numerical simulations describe the blast flow as a high-velocity pyroclastic density current generated by a rapid expansion (burst phase, lasting less than 20 s) of a pressurized polydisperse mixture of gas and particles and its subsequent gravitational collapse and propagation over a rugged topography. Model results show good agreement with the observed large-scale behavior of the blast and, in particular, reproduce reasonably well the front advancement velocity and the extent of the inundated area. Detailed analysis of modeled transient and local flow properties supports the view of a blast flow led by a high-speed front (with velocities between 100 and 170 m/s), with a turbulent head relatively depleted in fine particles, and a trailing, sedimenting body. In valleys and topographic lows, pyroclasts accumulate progressively at the base of the current body after the passage of the head, forming a dense basal flow depleted in fines (less than 5 wt.%) with total particle volume fraction exceeding 10−1 in most of the sampled locations. Blocking and diversion of this basal flow by topographic ridges provides the mechanism for progressive current unloading. On ridges, sedimentation occurs in the flow body just behind the current head, but the sedimenting, basal flow is progressively more dilute and enriched in fine particles (up to 40 wt.% in most of the sampled locations). In the regions of intense sedimentation, topographic blocking triggers the elutriation of fine particles through the rise of convective instabilities. Although the model formulation and the numerical vertical accuracy do not allow the direct simulation of the actual deposit compaction, present results provide a consistent, quantitative model able to interpret the observed stratigraphic sequence.